Branching Pattern of the Medial Calcaneal Neurovascular Bundle in Porta Pedis of the Human Foot - Khalid Musa Fadlelmula Awadelseid (International Journal of Human Anatomy, 2019)
The medial calcaneal nerve (MCN) is the first branch of the posterior tibial nerve (PTN) in the porta pedis, enervates the skin of the heel and medial side of the foot. Heel pain is a common condition encountered by physicians, and this may have a significant clinical association with the MCN’s branching pattern. This study was to identify branching pattern variations in the medial calcaneal neurovascular bundle. This study was carried out using 60lower limbs of formalin-embalmed cadavers, using the tarsal tunnel dissection method for 30right and 30 left lower limbs. The medial calcaneal neurovascular bundle course was identified by exposing the PTN and its branches from the distal end of the leg toward the plantar surface beyond its bifurcation and resecting the skin and flexor retinaculum. Many MCN branching pattern variations (specifically concerning origins, numbers, and levels of branching) were observed. In the right foot a single branch was present in 21 specimens (70%), while two branches were observed in nine specimens (30%). In the left foot, a single branch was present in 22 specimens (73.3%) and two branches were present in 8 specimens (26.7%). In this study, two branches originate from lateral planter artery is the most common observation. This study concludes that a single MCN originating from the TN is the most common variant. Two medial calcaneal arteries (MCAs) originating from the LPA is also common.
Keywords: Anatomy